Domestication strategies for the endangered catfish species pseudopimelodus mangurus valenciennes, 1835 (Siluriformes: Pseudopimelodidae) - Shiguemoto, G. F. [UNESP]; Arashiro, D. R. [UNESP]; Levy-Pereira, N.; Santos, S. C.A.; Senhorini, J. A.; Monzani, P. S.; Yasui, G. S. [UNESP] (FapUNIFESP (SciELO), 2021)
Wild fish domestication can be considered a strategic approach to endangered species conservation, supporting studies and reducing economic and environmental costs. Three of the most important strategies in the domestication processes of fish are the adaptation of wild fish to captivity, the reproduction of the adapted fish and the production and maintenance of the young individuals. That being said, the present study is divided in three experiments: the 1st aimed to adapt wild Pseudopimelodus mangurus to captivity environment using different feeding approaches and a prophylactic strategie; the 2nd aimed to reproduce the adapted individuals from the 1st experiment; and the 3rd aimed to train the P. mangurus juveniles to accept commercial diets. The 1st and 2nd experiments were successful at the maintenance and artificial reproduction of P. mangurus kept in tanks between the reproductive seasons. The results suggest that the reproductive performance of animals kept in captivity (initial relative fertility-IRF = 609.25 ± 36.6 eggs/g) was similar (p > 0,05) to the performance found in wild individuals (IRF = 679.21 ± 45.66 eggs/g). Feed training of P. mangurus juveniles (3rd experiment) was also conducted, evaluating three feeding treatments with different concentrations of bovine heart and ration. At the end of the experiment, the treatment containing half bovine heart and half commercial feeding resulted in the highest values of weight gain (0.10 ± 0.16 g), specific growth rate (0.37 ± 0.11 mm), length (47.78 ± 2.35 mm) and growth (2.15 ± 2.27 mm), suggesting reasonable acceptability to artificial diets in the cultivation of this species. As conclusion, the present study contributes with the development of techniques for the domestication of fresh water fish species with commercial value or andangered of extinction, showing the domestication and reproduction of wild P. mangurus in captivity. However, more studies have to be conducted in order to improve the acceptance of artificial feeding by juveniles and to increase their survival rate.
Estratégias de domesticação das espécies ameaçadas de peixe-gato pseudopimelodus mangurus valenciennes, 1835 (Siluriformes: pseudopimelodidae)
Keywords: Aquaculture; Artificial reproduction; Conservation; Feed training; Marbled catfish; Siluriforms